Effect of pulse frequency on the nanosecond pulsed laser welded Al/steel lapped joint. (November 2021) - Shu, Fengyuan; Niu, Sicheng; Zhu, Baohua; Wu, Laijun; Xia, Hongbo; Chen, Bo; Zhao, Junming; Tan, Caiwang
Highlights: Al and steel foils were successfully joined via nanosecond pulsed laser welding. Highest tensile shear force of 135.4 N was obtained at the frequency of 225 kHz. Three fracture modes obtained at different frequencies were elucidated. Two effects of pulse frequency on elemental diffusion were clarified. Abstract: Nanosecond pulse laser welding of 6063 aluminum alloy and 316L stainless steel sheets with a thickness of 0.2 mm was performed. The effect of pulse frequency on the joining characteristics was investigated. The results showed that porosities and cracking defects with larger dimension and numbers were produced in joints at the frequency of 125 kHz, while fewer defects were obtained in the joints with the pulse frequency larger than 175 kHz. As the pulse thermal effect played a major role at the frequency of 125 kHz, diffusion and enrichment of aluminum elements occurred in almost the entire aluminum side of the weld, generating various intermetallic compounds such as FeAl, Fe2 Al5 and FeAl3 . As the frequency increased, the banding structures in the weld became more congregate, which were mainly the mixed phases of FeAl and Fe2 Al5 . The shear force test results indicated that the highest shear force of 135.4 N was obtained when the pulse frequency was 225 kHz. The nailing effect of the wave-shaped weld structures and the absence of porosities led to desirable mechanical properties. Besides, three fracture modes, named by interfacial fracture (IF), substrate tearing failure (STF) and nugget pullout (NP), could be classified. The large interfacial porosities and dispersive distribution of brittle phases led to the IF mode. The distribution of the Fe-Al brittle phases at the weld edge resulted in the STF mode. The existence of microcracks at the bottom of the weld contributed to the NP mode.